Organoleptic Acceptance of Tempe Steak with Added Shrimp Shell Flour as a Food Innovation - Fathanah, Nurul; Djalal, Muspirah; Hasmiyani, Hasmiyani; Tahir, Mulyati M.; Asfar, Muhammad; Hidayat, Serli Hatul; Farahdiba, Andi Nur; Hatimah, Husnul (Jurnal Biologi Tropis, 2025)
Shrimp shells are commonly used as animal feed, but they actually have a savory taste and crispy texture, making them a potential ingredient in food products for human consumption. Shrimp shells also have high nutritional value, comparable to shrimp meat itself. This study aims to evaluate the organoleptic acceptance levels (color, aroma, texture, and taste) of tempe steak formulated with the addition of shrimp shell flour at various concentrations. The variations in shrimp shell flour concentration used in the formulation were 0%, 5%, 10%, 15%, and 20% of the total tempe weight. Each treatment was made into tempe and subjected to hedonic organoleptic test. The results showed that differences in shrimp shell flour concentration influenced panelist acceptance. The most preferred color of tempe steak made with the addition of shrimp shell flour was found at a concentration of 15%, while the best aroma, taste, and texture parameters were found at a concentration of 10%. However, the acceptance in same parameters was lower than that of no addition of shrimp shell flour, making it necessary for further research to find concentration with higher acceptance.